Plasma cortisol activity in rats under conditions of chronic stress supplemented with resveratrol (Colombia Medica, 2012)
Objective: Determine the activity of cortisol in rats treated with exogenous adrenocorticotropic hormone (ACTH) and a resveratrol supplement.Methods: Forty-eight adult male rats and 16 adult female rats (Rattus norvegicus) three months old with a body weight of 200 to 250 g and 300 to 350 g for both male and female were used and kept in controlled environmental conditions, temperature of 20±2° C and light-dark cycles of 14 and 10 hours. They were fed with balanced food and had free access to water. The rats were randomly divided into four groups: group 1, was treated with 5 μg/kg of ACTH i.p. every twelve hours; group 2, received the same treatment with ACTH plus a grape extract supplementation of 40 mg/kg; group 3, only received grape extract and group 4,served as control and only received saline solution (0.9%) i.p. The experimental was designed as a 2×2 factorial with two ACTH levels and two extract grape levels.Results: Significant differences were not found in cortisol concentrations for day, gender or treatment effects (0.75 μg/dL ± 0.11; p